ITS2 and 18S rRNA gene sequence-structure phylogeny of the Haptophyta (Haptista) - Louisa Ridder; Bente Edvardsen; Matthias Wolf (PLoS ONE, 2026)
The phylogeny of haptophytes, a diverse and ecologically significant group of microalgae, remains incompletely resolved despite extensive molecular studies. In this study, we apply a sequence-structure phylogenetic framework to the Haptophyta, utilizing ribosomal RNA (rRNA) small subunit (SSU) gene (18S; nearly complete sequences) and internal transcribed spacer 2 (ITS2) datasets. By integrating secondary structure information during sequence alignment and tree inference, we aim to enhance phylogenetic resolution and clarify evolutionary relationships within this lineage. Our taxon sampling reduced over 40,000 available 18S sequences to 396 representatives, alongside a compilation of 224 ITS2 sequences. Comparative modeling and homology-based structure prediction revealed both conserved and variable features in 18S and ITS2 secondary structures, with notable deviations in certain taxa. Maximum likelihood (ML) subset phylogenies based on 18S sequence-structure data showed the greatest congruence with established taxonomy, such as the division between calcifying and non-calcifying lineages. In contrast, ITS2 data presented alignment challenges due to high sequence variability, length differences, and limited taxon representation. Incorporating secondary structure information improved alignment quality and reduced phylogenetic artifacts, though ITS2 remained unsuitable for resolving deep relationships among haptophytes. Instead, ITS2 proved more valuable for distinguishing closely related species. While bootstrap support values were similar between sequence-only and sequence-structure approaches, the latter suggested alternative phylogenetic placements that better aligned with previous studies (using multiple markers or also some partial 18S sequences); for Hayaster perplexus in particular, these placements also better matched morphological data. Our results underscore the critical impact of taxon sampling and methodological choices on phylogenetic outcomes. Despite these challenges, the 18S sequence-structure ML tree offers a reliable depiction of haptophyte phylogeny, even though some backbone relationships remain weakly supported. Overall, this study highlights both the benefits and limitations of integrating RNA secondary structure into molecular phylogenetics and advances our understanding of haptophyte evolution.